Thermosets and composites : material selection, applications, manufacturing and cost analysis - Biron, Michel (William Andrew, 2014)
This book bridges the technology and business aspects of thermosets, providing a practical guide designed for engineers working in real-world industrial settings. The author explores the criteria for material selection, provides information on material properties for each family of thermosets, and discusses the various processing options for each material type. He explains advantages and disadvantages of using thermosets and composites in comparison to competing materials and assesses cost aspects, enabling the reader to balance out technical and economic constraints when choosing a thermos.
Keywords: Thermosetting plastics.; Plastics industry and trade.; elektronické knihy; electronic books